cDNA Microarray Technology for the Analysis of Gene Expression - Auesukaree, Choowong (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
DNA Microarray technology is a new and powerful tool for studying a genome-wide gene expression in many orgamism. This technology is a high throughput, highly parallel RNA expression assay technique that permits quantitative analysis of RNAs transcribed from both known and unknown genes. This review describes array manufacturing, experimental design, and its application to gene discovery and expression. Microarray technology id rapidly becoming a central platform for functional genomics. Keywords: microarray, gene expression, functional genomics Corresponding author: E-mail: choowonga@hotmail.com